Enhanced immersion two-phase liquid cooling thermal management for data centre - Teo, Jun Hong (Nanyang Technological University, 2021)
Jet impingement cooling was first introduced as a method to manage heat in the application of cooling gas turbine blades and vanes in the early 1960s. It was found to be a more effective way of cooling compared to convection cooling and hence, impingement jets gained popularity in the cooling of electronic component. Due to technology advancement, there is a need to dissipate large amount of heat fluxes. It was then explored by many investigators who wanted to further enhance the performance by combining it with pool boiling technique which gave rise to submerged jet impingement cooling method. This study investigated the heat flux generated which was experimentally obtained as the main parameter in determining the performance of heat transfer. A notable number of literature review pertaining to experimental and theoretical studies on heat transfer performance method was conducted and reported in this report. Several correlations were found to influence the performance of jet impingement cooling, such as, nozzle-to-plate height and therefore it is one of the important parameters looked into in this report. This report presents the experimentally obtained results of jet impingement cooling performance on a 20mm-by-20mm plain copper block which was heated by electrical power. A total of six sets of nozzle-to-plate ratio, were experimented on in this study. Further discussion on the effects of jet tube length and nozzle diameter size on heat transfer performance were analyse and review in the report as well. The experiment data substantiate that the average heat fluxes for smaller diameter choice at a fixed nozzle-to-plate height of 10.8mm and 14.4mm resulted in an improvement of 10 percent and 22 percent respectively. Furthermore, by opting for a shorter nozzle-to-plate height at fixed nozzle diameter size of 1mm and 2.4mm managed to result in an improvement of 3.9 percent and 11.5 percent, respectively. This study is aimed at determining the most influencing correlations that is most applicable for the consideration of future submerged jet impingement designs used in data centre data board cooling. Based on the experiment findings, potential areas for improvement for future works has been proposed by the author. The potential areas worth further research into are suggested at the end of the report, which include the use of a high-speed camera to capture bubbles flow on the boiling surface during the experiment and incorporating additional jets in the experiment as practical application of jet impingement cooling system will normally consist of a number of jets.